Outpatients' preference of communication medium for patient counseling in University of the Philippines-Philippine General Hospital - Cadorna, Kriza Rosette A.; Macalalad, Jesca Joi A.​; Santos, Krizza Camille M.​
With the advancement of technology, various communication media have been introduced for patient medication counseling to optimize patient-centered pharmaceutical care. However, there are limited studies that focus on the assessment of patients? preference to these communication media and its predictors. This study generally aimed to determine the preference of communication media used in patient counseling among outpatients in the University of the Philippines ? Philippine General Hospital (UP-PGH). It employed a descriptive, correlational design to describe outpatients in UP-PGH outpatient pharmacies, based on socio-demographic characteristics, level of knowledge on medication counseling, satisfaction of prior counseling experience, degree of willingness to be counseled by a pharmacist, and communication medium preference, and to determine if the factors are significant predictors for the preferred communication medium. Convenience sampling was done. A total of 192 patient respondents participated in the study. Results showed that majority are 41-60 years old (39.62%), female (84.92%), married (59.12%), from urban areas (70.44%), high school graduates (46.04%), unemployed (64.15%), and have an income below Php 20,000 (72.96%). Respondents have a high knowledge on patient counseling (mean=66.53 of 100.00, n=159), highly satisfied with their prior experience of patient counseling (mean=4.19 of 5.00, n=159), and are willing (68.55%) to be counseled by a pharmacist. Respondents have a high preference for face-to-face on five out of six criteria, while text message got the highest preference for ease of use. Overall, face-to-face has the highest level of preference. The best set of predictors for each medium were determined by regression analysis. No significant predictors were found for face-to-face. Educational attainment (p=.035) is a significant predictor for the preference for text message. Age (p=.002), knowledge score (p=.022) and place of residence (p=.035) are significant predictors for preference level for telephone. Preference level for online is predicted by education (p<.001), age (p<.001) and willingness (p=.004). Not all identified variables were found to be a significant predictor for outpatients? preference on the use of different communication media for patient counseling. As this study performed non-probability sampling, results cannot represent and generalize for the whole population. Furthermore, most of the respondents have only experienced face-to-face counseling, this may present selection bias. It is recommended to perform probability sampling, to explore other predictors for the communication medium preference and to recruit more patients with prior experience with other communication media. It is also recommended to incorporate other communication media in the counseling service of UP-PGH to maximize patient interaction while considering patients? characteristics to further cater patients? changing needs.